TINGGINYA BEBAN KERJA PERAWAT BERKORELASI LEMAH TERHADAP MEMANJANGNYA WAKTU TUNGGU TRANSFER PASIEN KE RUANG RAWAT INAP RUMAH SAKIT - Lia Christina; Sih Ageng Lumadi; Yeni Fitria (Jurnal Ilmiah Kesehatan Media Husada, 2020)
Introduction : Outpatient installation is a unit with a complex workload. Complex and high-rise jobs will affect the length of waiting time for services to patients that have an impact on service quality. This study was conducted to know the nurses' outpatient workload and the length of waiting time for transferred patient to the inpatient room. Method: The research method is descriptive analytic observational. The samples of the study were 92 outpatients taken by purposive sampling. Data collection uses sampling work methods. Hypothesis testing uses the C contingency coefficient with the results of almost all respondents; (81.5%) with high workloads and more than half (64%) with a waiting time of> 3 hours. Results and Analysis: The results showed that the value of ρ Cramer was 0.030 (ρ <0.05), the coefficient value was 0.221; the strength of correlation is weak however, it has positive correlation. It can be concluded that there is a significant correlation between nurses' outpatient workload and the length of waiting time of the transferred patient to the inpatient room at Batu Baptist Hospital. Discussion: The higher the workload that the nurse has, the longer the waiting time for transfered patient to the inpatient ward. The Hospital needs to reexamine the employee need based on duties and authority and there must be special officers in the process of hospitalization in outpatient care. Keywords : Nurse Workload, Length of waiting time for patient transfer